Evaluation of autonomic nervous system functions by using tilt table test and heart rate variability in epileptic children - AKALIN, FİGEN (My University, 2023)
Objective: The value of head-up tilt test (HUTT) for differential diagnosis of epilepsy and the autonomic nervous system functions in epileptic children using heart rate variability (HRV) are studied. Patients and Methods: The study group consisted of 16 children with idiopatic/criptogenic epilepsy and 12 controls. Heart rate, PR interval, corrected QT (QTc) interval, QT and QTc dispersion were calculated using 12-lead electrocardiogram (ECG), HRV analysis was performed using the Holter recordings obtained both during HUTT and throughout the day. Time domain parameters, standard deviation of all RR intervals (SDNN), the standard deviation of mean NN intervals in five-minutes recording (SDANN), mean standard deviation of NN intervals in five-minutes recordings (SDNNi), root mean square of successive differences (RMSSD), count divided by the total number of all NN intervals (pNN50) and frequency domain parameters low frequency (LF), high frequency (HF), low-frequency/high-frequency ratio (LF/HF) were calculated in both and compared between the two groups.Results: Head-up tilt test was positive in 4 epileptic children (25%), none of controls were positive. The heart rate of the patients were higher than the controls (p=0.015). LF/HF ratio in 24-hour Holter recordings, were significantly lower (1.13 +/- 0.6, 1.83 +/- 0.7 respectively, p=0.002); the SDANN during HUTT (28.7 +/- 20.2, 18.2 +/- 19.9 respectively, p=0.024) were significantly higher in the patients than the controls.Conclusion: Head-up tilt test positivity is frequent in epileptic children, and cannot be used in differential diagnosis. HRV calculated both from 24 hour Holter recordings and Holter recordings under orthostatic stress were impaired in favour of parasympathetic system in epileptic children.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Epilepsy; Syncope; Head-up tilt test; Heart rate variability; Autonomous nervous system; Arrhythmia; ECG-CHANGES; SEIZURES; SPECTRUM: Epilepsy; Syncope; Head-up tilt test; Heart rate variability; Autonomous nervous system; Arrhythmia